Effect of High-Temperature Quenching on the Phase Composition, Structure, and Wear Resistance of Ni-Hard Chromium-Nickel Cast Iron - Filippov M.A. (EDP Sciences, 2021)
Metallographic, micro-X-ray spectral and X-ray structural analyses have been carried out. The quenching temperature increase from 900 to 1150 °C leads to high abrasive wear resistance in Ni-hard chromium-nickel cast iron. The initial hardness decreased before the test from 60 to 35 HRC due to the fact that the phase composition of the metal base before the wear test changes during quenching from medium-carbon martensite with secondary cementite to retained metastable austenite. It contributes to increase the crack resistance of cast iron. Austenite turns into dispersed friction martensite on the working surface in the process of wear testing or operation, as a result of the impact of abrasive particles. This martensite together with a part of cementite provides a high level of hardening and operability of the cast iron secondary microstructure.